2009
DOI: 10.1111/j.1439-0329.2008.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of endophytic Biscogniauxia mediterranea to variation in leaf water potential of Quercus cerris

Abstract: Endophytic behaviour of Biscogniauxia mediterranea, the causal agent of charcoal disease of oak, was studied over two growing seasons on Quercus cerris in a forest in central Italy. Isolation of the fungus from asymptomatic tissues varied with tissue type, period of sampling and year. Presence of the fungus in asymptomatic plants was significantly higher in fall, compared with that in spring and summer. However, a significant effect of tissue water content on the presence of B. mediterranea was recognized. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…Another recent study on Pinus brutia indicated that, as moisture availability decreased, the highest correlations of tree growth with rainfall were obtained for progressively longer integration periods (from 1-2 y in moist periods to 5-6 y during the actual severe drought), suggesting increasing dependency on deep soil water (Sarris et al, 2007). Endophytic attacks may therefore be favored by reduced formation of latewood and increased cavitation, allowing fungi to reach the cambium (Vannini et al, 2009). Climatic conditions that alternate from greatly favorable to unfavorable, as was the case from pre-to post-1997, have also been proposed as the trigger of forest growth decline in dense stands that experience high competition levels (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study on Pinus brutia indicated that, as moisture availability decreased, the highest correlations of tree growth with rainfall were obtained for progressively longer integration periods (from 1-2 y in moist periods to 5-6 y during the actual severe drought), suggesting increasing dependency on deep soil water (Sarris et al, 2007). Endophytic attacks may therefore be favored by reduced formation of latewood and increased cavitation, allowing fungi to reach the cambium (Vannini et al, 2009). Climatic conditions that alternate from greatly favorable to unfavorable, as was the case from pre-to post-1997, have also been proposed as the trigger of forest growth decline in dense stands that experience high competition levels (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of fungal DNA was significantly higher during the vegetative season (summer) in both sampled forests. From an ecological point of view, B. nummularia behaves in a similar way to B. mediterranea, which proliferates in asymptomatic tissues of Q. cerris during dry growing seasons (Vannini et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The ability of latent pathogens to quickly adapt to new environmental conditions suggests that these organisms could be used as bioindicators of forest health ( Vannini et al 2009, Romeralo et al 2012), in that: (i) their presence can be easily detected; (ii) they are sufficiently sensitive to provide an early warning of change; (iii) iForest 9: 49-54 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations